Discourse Structure of Classroom Session During Covid-19 Pandemic - Laily Rahmatika; Malikatul Laila (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The case of discourse classroom session during Covid-19 pandemic is conducted online might contain different and various structures. The study aims are to identify the typical structure of classroom session. This study is in the domain of qualitative using a Conversation Analysis (CA) approach. Data were series of utterances in classroom sessions. Data sources were taken from lecturers and students speech in the activity of classroom sessions. Data sources were taken from lecturers and students’ speech in the activity of classroom sessions conducted mainly by Indonesian and foreign lectures through Google Meet and Zoom. Data collection was carried out using recording, note-taking, and interpreting techniques from the video process activity through Google Meet and Zoom operations. Data analysis uses comprehensive interpretation and reflection techniques. The results show that typical discourse structure of classroom session is I-C-CI (Introduction-Content-Closing), while this has five variations such as I:G-C-QA-CI:F, I:C-C:PM-CI:OF, I:G-C:P-CI:OF, I:G-C:PM-CI:GI, I:P-C:PM-CI:C.